All That Was Lost. German Life in Kafka’s Prague Before World War I, During the War, and At Its End (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2017)
In this paper I want to trace briefly how Franz Kafka reacted to some salient cultural features of his time. I will select segments of his writings which I believe reflect his view, or even his characterization of the three main historical periods he lived through: pre-World War I, the war years 1914 to 1918, and five and one half of the postwar years. Of course, this is by no means a complete, thorough discussion of those periods and his works that I mention.